Repertoar Bahasa Masyarakat Transmigran Desa Bandung Jaya dalam Perspektif Tindak Tutur Sebagai Implikasi Pemertahanan Bahasa : Language Repertoire of the Bandung Jaya Village Transmigrant Communityin the Perspective of Speech Action as an Implication of Language Defense - Fajarini, Indah; Arif Fadhilah, Muhammad; Hariadi, Joko; Taufik Hidayat, Muhammad; Liasna, Tanita (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to do the following: 1) Describe the language repertoire used by the transmigrant community in Bandung Jaya Village by considering the perspective of speech acts. The objectives of this research are as follows. 2) Describe the use of language in the transmigrant community in Bandung Jaya Village from the perspective of speech acts, and 3) Describe the scope of its implications for the preservation of the language of the transmigrant community in Bandung Jaya Village. This research is a qualitative research. Data was collected through observation methods with interview techniques, questionnaires, involvement, recording, and observation. The data were analyzed using a descriptive method. The results of the study show that; 1) The language repertoire of the transmigrant community in Bandung Jaya Village consists of: a) As many as 30% of the community only masters one language, namely BJ (15%), BS (10%), and BA (5%). b) As many as 55% of the people speak two languages, namely BJ and BI (25%), BS and BI (20%). c) As many as 15% of people speak more than two languages, namely BJ, BS, and BI (5%), as well as BJ, BS, BI, and BA (5%). 2) The use of language in the transmigrant community in Bandung Jaya Village was analyzed through conversation with a speech action approach, which functions as a matrix of repertoire - code or speech style. According to Searle, speech acts are classified into five main functions, namely: (a) directive function, (b) representative function, (c) expressive function, (d) declarative function, and (e) commissive function. (3) The implications of preserving other languages on the language of the transmigrant community itself in terms of social and cultural aspects. This can be seen from the perspective of cultural identity that affects language as an important part of the identity of transmigrant people. Social integration Transmigrant communities also have to balance maintaining their mother tongue and adapting to the majority language in the new area. Changes in language patterns that occur in the younger generation in the transmigrant community may prefer to use the national or majority language, which can threaten the existence of their mother tongue.